2009
DOI: 10.1007/s11224-009-9430-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular associations in acacia gums

Abstract: The tendency of polysaccharides to associate in aqueous solution has long been recognised. Molecular associations can profoundly affect their performance in a given application due to its influence on the molecular weight, shape and size. This will ultimately determine how the molecules will interact with each other, with other molecules and with water. There are several factors, such as hydrogen bonding, hydrophobic association, ion mediated association, electrostatic interaction, concentration dependence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 33 publications
1
51
0
1
Order By: Relevance
“…High-pressure homogenization treatment can be used for breaking some molecular association and making a higher proteinaceous fraction available to better emulsification properties. [40] It is noteworthy that droplet size distributions (volume percentage) of emulsions in all GA concentration were mono-peaked, while PG emulsions with more than 1.5% were bimodal (Fig. 5).…”
Section: Effect Of Gum Concentrationmentioning
confidence: 89%
“…High-pressure homogenization treatment can be used for breaking some molecular association and making a higher proteinaceous fraction available to better emulsification properties. [40] It is noteworthy that droplet size distributions (volume percentage) of emulsions in all GA concentration were mono-peaked, while PG emulsions with more than 1.5% were bimodal (Fig. 5).…”
Section: Effect Of Gum Concentrationmentioning
confidence: 89%
“…In that context, Al-Assaf et al (2009) observed that the protein-arabinogalactan fraction of a proteinpolysaccharide complex was responsible for the emulsifying activity of gum arabic.…”
Section: Bg Centesimal Compositionmentioning
confidence: 99%
“…Biomaterials polymers were also used [10], [11]. Bioactive porous networks of titanium dioxide templated with collagen for drug delivery was also employed [12], [13], [14], [15], [16].…”
Section: Introduction:-mentioning
confidence: 99%